Ethnopharmacological study of medicinal plants used for chronic diseases treatment in Rabat-Sale-Kenitra region (Morocco) - El Hachlafi, Naoufal; Chebat, Abderrahim; Soulaymani Bencheikh, Rachida; Fikri-Benbrahim, Kawtar (Ethnobotany Research and Applications, 2020)
Background: This work aims to the valorization of resources in the provinces of Rabat-Sale-Kenitra region, particularly aromatic and medicinal plants, and to the collection and documentation of the new ethno-medico-botanical information concerning the traditional use of these medicinal plants against chronic disease. Methods: An ethnobotanical survey was conducted in Rabat-Sale-Kenitra region with traditional herbalists, on one hand, and with subjects suffering from chronic diseases on the other hand, during 5 months from February to June 2019. Data were collected thanks to 581 questionnaire cards based on semi-structured interviews. Relative Citation Frequency (RFC), Family Importance Value (FIV), Plant Part Value (PPV), Fidelity Level (FL), and Informant Consensus Factor (ICF) were used in ethnobotanical data analysis. Results: A total of 79 medicinal and aromatic plant species were identified, belonging to 74 genera and 39 botanical families, of which Lamiaceae (FIV=0.038) and Asteraceae (FIV=0.015) were the most frequently represented. The most cited plant species were Nigella sativa (RFC=0.12), and Origanum compactum (RFC= 0.091). Leaves represent the most used plants part with PPV=0.246 and decoction was the major preparation model of remedies (37.7%). Concerning treated diseases, chronic kidney disease has the highest ICF (0.93). Furthermore, 18 cases of side effects related to the use of medicinal species such as Aristolochia longa and Peganum harmala were recorded. Conclusion: In light of this work, the population recognizes the effectiveness of medicinal plants in the treatment of chronic diseases, but their use will have to go through extensive phytochemical, pharmacological and toxicological research in order to clarify their effectiveness and innocuousness. Keywords: Medicinal and aromatic plants, Ethnobotanical surveys, Chronic diseases, Rabat-Sale-Kenitra region.